The student voice: Using student feedback to inform quality in higher education - Tucker, Beatrice M. (Curtin University, 2015)
This thesis presents a scholarly synthesis of a series of original published works providing evidence that student feedback, collected and analysed using valid and defensible methods, is effective in improving the quality of teaching and learning in higher education. The key factors underpinning the effective use of student feedback for quality improvement of teaching and learning in higher education are revealed. Students’ perceptions of their experience in achieving learning outcomes are reported.